Excellence in agronomy 2030 - project launch - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2020)
Excellence in Agronomy 2030 "Delivering agronomic gain at scale for the Sustainable Intensification of smallholder farming systems in the Global South" - Project launch at the AGRF virtual summit 2020